A Novel Strategy for Synthesis of Polystyrene/Fe3O4 Nanocomposite: RAFT Polymerization, Functionalization, and Coordination Techniques. Issue 8 (24th May 2017) - Massoumi, Bakhshali; Mousavi-Hamamlu, Seyyede-Vahhajeh; Ghamkhari, Aliyeh; Jaymand, Mehdi
ABSTRACT: A facile strategy for the synthesis of polystyrene/Fe3 O4 nanocomposite is suggested. For this purpose, styrene and 4-chloromethyl styrene monomers was copolymerized through reversible addition of fragmentation chain transfer technique [P(St- co -CMSt)] and then the chlorine groups of CMSt units were converted to diethyl malonate groups through a nucleophilic substitution reaction. Afterward, esteric groups of diethyl malonate were hydrolyzed to afford carboxylic acid-functionalized polystyrene. This polymer with carboxylic acid groups can adsorbed onto the surface of Fe3 O4 nanoparticles through the interaction with hydroxyl groups onto the surface of the nanoparticles. We envision that the synthesized PSt/Fe3 O4 nanocomposite may be find applications in electromagnetic interference shielding and environment sciences. GRAPHICAL ABSTRACT: